Bioherbicidal effects of batawali leaf extract on weed control, and rice growth and yield - Noor Mohamad, Noor Hafifi (2015)
Synthetic chemicals have been the only economical way to control weeds for the longest time. Nevertheless, the side effects of using chemical means are undeniably harmful towards humans and nature. This study was done to look for alternative for these harmful chemicals by using natural chemical or allelochemicals, in this case using T. tuberculata (Batawali) leaves extract as the applied herbicide on rice production. The effect of T. tuberculata leaves extract on weed control, rice growth and yield were studied on four different varieties namely MR219, MR220, MR263, and MR269 under glasshouse condition in Ladang 10, UPM. As expected in the result, weed control by this herbicide was excellent and the side effect on growth and yield were minimum. The only variety that was significantly affected by T. tuberculata application was MR219, which the growth of the variety particularly on its height was affected in the beginning but on yield part, no significant effect was recorded. As for the conclusion, the application of this natural herbicide had significant effects on growth and yield mainly on latest and popular varieties such as MR220, MR263 and MR269.